2004
DOI: 10.1177/0091270004269518
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics/Pharmacodynamics of Desloratadine and Fluoxetine in Healthy Volunteers

Abstract: The authors assessed the potential for a pharmacokinetic/pharmacodynamic interaction between desloratadine and fluoxetine. This randomized, placebo-controlled, open-label study was conducted in 54 healthy volunteers. Subjects received 1 of 3 treatments: desloratadine 5 mg plus fluoxetine 20 mg, desloratadine 5 mg plus placebo, or fluoxetine 20 mg plus placebo. Serial electrocardiograms (ECGs) were performed at baseline and day 35. Treatment effects on C(max) and AUC were assessed. During coadministration of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 21 publications
(33 reference statements)
2
5
0
Order By: Relevance
“…2) Loratadine may have been metabolized via CYP2D6 to a metabolite other than desloratadine. This is consistent with the observation that coadministration of desloratadine with a potent inhibitor of CYP2D6 (fluoxetine) did not cause significant changes in the plasma concentrations of desloratadine (Gupta et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2) Loratadine may have been metabolized via CYP2D6 to a metabolite other than desloratadine. This is consistent with the observation that coadministration of desloratadine with a potent inhibitor of CYP2D6 (fluoxetine) did not cause significant changes in the plasma concentrations of desloratadine (Gupta et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…2) Loratadine may have been metabolized via CYP2D6 to a metabolite other than desloratadine. This is consistent with the observation that coadministration of desloratadine with a potent inhibitor of CYP2D6 (fluoxetine) did not cause significant changes in the plasma concentrations of desloratadine (Gupta et al, 2004).In this in vivo study, we did not evaluate the effect of CYP3A4 polymorphisms, due to the relatively low prevalence of the mutant alleles in Chinese populations as well as their uncertain function in vivo. Previous studies showed that CYP3A4 inhibitors such as clarithromycin (Carr et al, 1998), erythromycin (Brannan et al, 1995, and ketoconazole (Kosoglou et al, 2000) significantly increased the plasma concentrations of loratadine.…”
supporting
confidence: 85%
“…dmd.aspetjournals.org (Cingi et al, 2013). All other relevant studies have examined the pharmacodynamic/pharmacokinetic interaction potential of desloratadine with CYP2D6 and CYP3A4 substrates, and desloratadine was found to have limited potential for drug-drug interactions (Gupta et al, 2001(Gupta et al, , 2004Banfield et al, 2002aBanfield et al, , 2002b. With respect to special populations, patients with moderate hepatic impairment have been shown to have elevated levels of desloratadine (2.4-fold increase in area under the curve); however, it has been reported that 3-hydroxydesloratadine exposure was similar between hepatically impaired and normal patients (Gupta et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Few clinical studies have been performed to evaluate desloratadine as an inhibitor of CYP2D6 or CYP3A4. Desloratadine does not affect the pharmacokinetics of fluoxetine or azithromycin to a clinically significant extent (Gupta et al, 2001;Gupta et al, 2004). The previously reported requirement of UDPGlcUA in 3-hydroxydesloratadine formation led us to investigate the perpetrator potential of desloratadine toward 10 UGT enzymes expressed in liver (namely, UGT1A1, UGT1A3, UGT1A4, UGT1A6, UGT1A9, UGT2B4, UGT2B7, UGT2B10, UGT2B15, and UGT2B17) and three UGT enzymes expressed in the gastrointestinal tract (namely, UGT1A7, UGT1A8, and UGT1A10) (Parkinson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%